3008 Role of Interferon-gamma in Natural Clearance of Chlamydia trachomatis Infection in Women. (27th March 2019) - Jordan, Stephen; Coss, Lisa; Wilson, Landon; Barnes, Stephen; Geisler, William; Nelson, David
Abstract : OBJECTIVES/SPECIFIC AIMS: Chlamydia trachomatis (CT) infection can lead to reproductive morbidity in women. Animal models suggest that protection against CT is mediated through the cytokine interferon-gamma (IFN-γ), produced by CD4+ T-cells, which clears CT through intracellular tryptophan depletion. In humans, correlates of protection remain to be elucidated, which hinders chlamydia vaccine development. Natural clearance of CT infection (e.g., clearance before antibiotics) may be an immunological correlate of protection, evidenced by (1) CT clearance without antibiotics; and (2) a 4-fold reduced risk of CT reinfection within 6 months. We have identified women with and without natural clearance of CT infection. By comparing these two groups of women, the role of IFN-γ-mediated natural clearance of CT infection will be investigated. METHODS/STUDY POPULATION: Through collaboration with a cohort study of CT-infected women, we have access to stored specimens from women who naturally cleared CT or had persisting CT infection. Using peripheral blood mononuclear cell (PBMC), we will assess whether natural clearance of CT infection is associated with IFN-γ-producing CD4+ T-cells by stimulating PBMC ex vivo with CT antigens using intracellular cytokine staining. We will also use cervicovaginal lavage (CVL) and untargeted High-Performance Liquid Chromatography-Mass Spectrometry to assess for tryptophan-dependent and -independent metabolic pathways associated with natural clearance of CT infection. RESULTS/ANTICIPATED RESULTS:: To date, IFN-γ has been measured in 10 women who did not clear CT infection, demonstrating that <20% of these women produced significant levels of IFN-γ. Women who naturally cleared CT have yet to be studied. Untargeted HPLC-MS has been performed on 6 women (3 who cleared matched to 3 with persisting CT infection). To date, 11 pathways that are significantly associated with natural clearance have been identified. DISCUSSION/SIGNIFICANCE OF IMPACT: The outcome of natural clearance of CT infection is distinct from women with persisting chlamydia. These studies may inform whether IFN-γ, produced by CD4+ T-cells, or tryptophan-dependent or -independent metabolic pathways are associated with natural clearance, which may advance chlamydia vaccine development.